Saphenous vein graft aneurysm and fistula with compression mimicking mitral stenosis. (4th January 2018) - Ziffra, Jeffrey B; Tran, Phillip; Strattan, Melody; Cookman, Brock
Abstract : We present the case of a patient who presented with acute coronary syndrome and was found to have a mass compressing the left atrium. An angiogram revealed a large saphenous vein graft aneurysm with a fistula into a cardiac chamber, presumed to be the left ventricle. The patient also developed a functional mitral stenosis secondary to this mass causing left atrial compression. The patient passed away prior to receiving surgery. We describe a rare case of venous graft aneurysm with compression and fistula to a chamber other than the right atrium, that to our knowledge has yet to be reported.